Generalized lichen planus in childhood: is dapsone an effective treatment modality? - Başak, Pınar Y.; Başak, Kayhan (The Turkish Journal of Pediatrics, 2002)
Childhood lichen planus is generally atypical in appearance, prolonged in duration and resistant to therapy. Moreover, the risk in administration of systemic drugs because of several adverse effects limits their use and effective therapy remains a problem in this age group. We report a case of generalized lichen planus in a nine-year-old boy with oral mucosa and nail involvement who was treated with dapsone.
Keywords: lichen planus; childhood; treatment; dapsone